Effect of Hot Blanching Treatment on the Quality and Storage Stability of Whole-wheat Fresh Noodles - WANG Jin-peng; LU Qi-shuai; LI Hong-yan; SUN Chun-rui; HOU Han-xue; LI Man; MA Meng; SUN Qing-jie (Liang you shipin ke-ji)
In order to improve the quality and storage stability of whole-wheat products, the effects of instantaneous hot blanching treatment at different temperatures (60~90 ℃) on the macro quality, micro characteristics, and storage stability of whole-wheat fresh noodles were investigated. Compared with the control (25 ℃), the cooking loss and water absorption of whole- wheat fresh noodles after hot blanching treatment were significantly reduced, and the longitudinal tensile strength increased. Hardness and chewiness of cooked noodles increased for 90 ℃ treated group. The images of scanning electron microscopy showed that the surface of whole-wheat fresh noodles prepared by hot blanching treatment was denser. The gluten network agglomeration was more obvious and the combination with starch granules was much closer with increasing temperature. The starch granules were intact and did not swell significantly. Hot blanching treatment increased the degree of gluten protein polymerization in whole-wheat fresh noodles, and the yield of glutenin-gliadin aggregates significantly increased with the increase of temperature. The content of α-helix and random coil increased, and the content of β-angle decreased. In addition, the shelf life of whole wheat fresh noodles after hot blanching treatment above 80 ℃ was extended by more than 2 times, and the browning of fresh noodles can be suppressed to a certain extent.